Positioning women's and children's health in African union policy-making: a policy analysis - Toure Kadidiatou; Sankore Rotimi; Kuruvilla Shyama; Scolaro Elisa; Bustreo Flavia; Osotimehin Babatunde (BMC, 2012)
Abstract Background With limited time to achieve the Millennium Development Goals, progress towards improving women's and children's health needs to be accelerated. With Africa accounting for over half of the world's maternal and child deaths, the African Union (AU) has a critical role in prioritizing related policies and catalysing required investments and action. In this paper, the authors assess the evolution of African Union policies related to women's and children's health, and analyze how these policies are prioritized and framed. Methods The main method used in this policy analysis was a document review of all African Union policies developed from 1963 to 2010, focusing specifically on policies that explicitly mention health. The findings from this document review were discussed with key actors to identify policy implications. Results With over 220 policies in total, peace and security is the most common AU policy topic. Social affairs and other development issues became more prominent in the 1990s. The number of policies that mentioned health rose steadily over the years (with 1 policy mentioning health in 1963 to 7 in 2010). This change was catalysed by factors such as: a favourable shift in AU priorities and systems towards development issues, spurred by the transition from the Organization of African Unity to the African Union; the mandate of the African Commission on Human and People's Rights; health-related advocacy initiatives, such as the Campaign for the Accelerated Reduction of Maternal Mortality in Africa (CARMMA); action and accountability requirements arising from international human rights treaties, the Millennium Development Goals (MDGs), and new health-funding mechanisms, such as the Global Fund to Fight AIDS, Tuberculosis and Malaria. Prioritization of women's and children's health issues in AU policies has been framed primarily by human rights, advocacy and accountability considerations, more by economic and health frames looking at investments and impact. AU policies related to reproductive, maternal, newborn and child health also use fewer policy frames than do AU policies related to HIV/AIDS, tuberculosis and malaria. Conclusion We suggest that more effective prioritization of women's and children's health in African Union policies would be supported by widening the range of policy frames used (notably health and economic) and strengthening the evidence base of all policy frames used. In addition, we suggest it would be beneficial if the partner groups advocating for women's and children's health were multi-stakeholder, and included, for instance, health care professionals, regional institutions, parliamentarians, the media, academia, NGOs, development partners and the public and private sectors.